Widened Dorsum: Bony and Cartilaginous Contributions - Linkov, Gary; Branham, Gregory (Facial Plastic Surgery, 2018)
Creation of a pleasing dorsal nasal profile in the anterior and lateral views requires proper analysis and planning to determine the required series of steps to accomplish the desired outcome. The widened nasal dorsum is a common esthetic complaint of the patient seeking rhinoplasty. Often patients seek an unrealistic result that, if accomplished, would leave them with a restricted nasal vault and nasal airway compromise. Nasal function must be balanced with the patient and surgeon's desire to narrow the nasal dorsum. Various techniques are used to control the width of the upper third, or bony vault, and middle third, or cartilaginous vault.
Keywords: widened dorsum; bony vault; cartilaginous vault